Penggunaan Model Pembelajaran Problem Based Learning (PBL) Dalam Meningkatkan Kemampuan Bercerita Siswa Kelas II MIS PUI Gereba - Permana Rahman, Aditya; Nursobah, Asep; Acim, Acim (Journal of Elementary Education: Strategies, Innovations, Curriculum, and Assesment, 2025)
Storytelling ability is an essential student capability that can be enhanced through relevant learning methods. This research, therefore, aims to optimize the storytelling skills of second-grade students at MIS PUI Gereba by implementing the Problem-Based Learning (PBL) model. Using a quantitative approach with a four-cycle Classroom Action Research (CAR) design, the study measures the model's effectiveness. The results demonstrate a significant improvement in students' storytelling abilities. The average student score increased from 62 in the first cycle to 85 in the fourth cycle. Student engagement also rose dramatically, from 65% in the first cycle to 90% in the final cycle. Thus, it is concluded that the PBL model is highly effective in enhancing the storytelling skills of second-grade students at MIS PUI Gereba. The model proves successful by providing a platform for students to practice critical thinking, explore ideas, and construct more structured and engaging narratives. Furthermore, collaboration within PBL groups effectively boosts students' comprehension, creativity, and confidence when presenting their stories.